ChemInform Abstract: An Efficient Organocatalytic Enantioselective Michael Addition of Aryl Methyl Ketones with 2‐Furanones: Highly Functionalized Chiral 3, 4‐Substituted Lactones. Issue 22 (13th May 2013) - Wang, Wei; Wang, Junfeng; Zhou, Shuo; Sun, Qi; Ge, Zemei; Wang, Xin; Li, Runtao
Abstract The title reaction provides a convenient access to a wide variety of highly substituted chiral γ‐lactones with good yields and good to excellent enantioselectivities (22 examples).